Time-Order Errors in Duration Judgment Are Independent of Spatial Positioning - Harrison, Charlotte; Binetti, Nicola; Mareschal, Isabelle; Johnston, Alan (Frontiers in Psychology, 2017)
Time-order errors (TOEs) occur when the discriminability between two stimuli are affected by the order in which they are presented. While TOEs have been studied since the 1860s, it is unknown whether the spatial properties of a stimulus will affect this temporal phenomenon. In this experiment, we asked whether perceived duration, or duration discrimination, might be influenced by whether two intervals in a standard two-interval method of constants paradigm were spatially overlapping in visual short-term memory. Two circular sinusoidal gratings (one standard and the other a comparison) were shown sequentially and participants judged which of the two was presented for a longer duration. The test stimuli were either spatially overlapping (in different spatial frames) or separate. Stimulus order was randomised between trials. The standard stimulus lasted 600ms, and the test stimulus had one of seven possible values (between 300-900ms). There were no overall significant differences observed between spatially overlapping and separate stimuli. However, in trials where the standard stimulus was presented second, TOEs were greater, and participants were significantly less sensitive to differences in duration. TOEs were also greater in conditions involving a saccade. This suggests there is an intrinsic memory component to two interval tasks in that the information from the first interval has to be stored; this is more demanding when the standard is presented in the second interval. Overall, this study suggests that while temporal information may be encoded in some spatial form, it is not dependent on visual short-term memory.